Oenin/Syringic Acid Copigmentation: Insights From a Theoretical Study - Li, Yunkui; Prejanò, Mario; Toscano, Marirosa; Russo, Nino (Frontiers in Chemistry, 2019)
On the basis of the dispersion-corrected density functional theory, a computational model is proposed to describe the oenin/syringic acid copigmentation and to explore the non-covalent interaction between the anthocyanin and the copigment in the framework of implicit solvent approach. The predicted binding free energy and visible spectrum shift of this copigmentation complex are in accordance with the experimental observations. The used model provides a good structural description of oenin/syringic acid complex and suggests that the intermolecular hydrogen bonding, in which the hydroxyl-rich sugar moiety in oenin plays a key role, may be the determinant for the formation and nature of the copigmentation complex.